ChemInform Abstract: 6, 6′‐Dihydroxy Terpyridine: A Proton‐Responsive Bifunctional Ligand and Its Application in Catalytic Transfer Hydrogenation of Ketones. Issue 18 (11th April 2013) - Moore, Cameron M.; Szymczak, Nathaniel K.
Abstract The Ru(III) terpyridine complex shown efficiently catalyzes the chemoselective transfer hydrogenation of a variety of ketones.